2007
DOI: 10.1590/s0102-311x2007000700016
|View full text |Cite
|
Sign up to set email alerts
|

Attributable fraction of work accidents related to occupational noise exposure in a Southeastern city of Brazil

Abstract: Noise is the most frequent type of occupational exposure and can lead to both auditory and extra-auditory dysfunction as well as increasing the risk of work accidents. The purpose of this study was to estimate the attributable fraction of work accidents related to occupational noise exposure in a medium-sized city in Southeast Brazil. In this hospital-based case-control study, including 600 cases and 822 controls, the odds ratio of work accidents (controlled for several covariables) was obtained classifying oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Furthermore, they demonstrated an association between noise and other kinds of alterations like the effect of noise in some hormones and electrolytes and the increase in occupational injuries. In this way, Dias and Cordeiro[48] showed that the calculated attributable fraction between noise and work accidents was 30%, and Barreto et al . [49] demonstrated that the risk of fatal injury related to work increased with the intensity of exposure to noise ( P =0.004).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, they demonstrated an association between noise and other kinds of alterations like the effect of noise in some hormones and electrolytes and the increase in occupational injuries. In this way, Dias and Cordeiro[48] showed that the calculated attributable fraction between noise and work accidents was 30%, and Barreto et al . [49] demonstrated that the risk of fatal injury related to work increased with the intensity of exposure to noise ( P =0.004).…”
Section: Discussionmentioning
confidence: 98%
“…However, limitations existed in these studies. The overall relationship is not well understood because these results were confined to a few industrial sectors (Amjad-Sardrudi et al, 2012; Barreto, Swerdlow, Smith, & Higgins, 1997; Cantley et al, 2015; Cohen, 1973b; Lees et al, 1980; Moll van Charante & Mulder, 1990; Picard, Girard, Simard, et al, 2008; Sbihi, Davies, & Demers, 2008), relied on worker’s opinion or recall (Clausen et al, 2009; d’Errico & Costa, 2012; Dias & Cordeiro, 2007, 2008; Melamed, Luz, & Green, 1992), or were not adjusted for age or experience (Barreto et al, 1997; Dias & Cordeiro, 2008; Melamed et al, 1992; Moll van Charante & Mulder, 1990) or occupation or safety hazard (Amjad-Sardrudi et al, 2012; Girard et al, 2009; Kling et al, 2012; Lees et al, 1980; Melamed et al, 1992; Moll van Charante & Mulder, 1990; Picard, Girard, Courteau, et al, 2008; Picard, Girard, Simard, et al, 2008; Sbihi et al, 2008; Yoon et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found associations between high noise exposures and injury, and have estimated that 12%-63.9% of workplace accidents in the industries studied were attributable to noise exposure or NIHL (Dias and Cordeiro, 2008, 2007; Picard et al, 2008)Researchers have also documented associations between noise exposure and occupational fatalities (Barreto et al, 1997; Melamed and Froom, 2002; Melamed et al, 2004). A potential association between hearing loss and injury has also been identified in workers (Cantley et al, 2015; Girard et al, 2014) including firefighters (Ide, 2007).…”
Section: Introductionmentioning
confidence: 98%